Perceived role of pharmacists in managing home-based pharmaceutical services in Norway: an interview study with community pharmacists - Bustic, Ivana; Zimonjić, Ivana; Marinkovic, Valentina (Archives of Pharmacy, 2025)
Pharmacists have the potential to address gaps in primary healthcare by providing pharmaceutical services in home care settings, particularly in response to the challenges faced by the Norwegian healthcare system. Their integration into primary care teams could enhance care quality, reduce the burden on physicians, and improve treatment accessibility and efficiency, as demonstrated in other countries. This study explores pharmacists’ perspectives on the challenges and opportunities associated with implementing pharmaceutical home care services in Norway, considering international experiences and trends. A qualitative study was conducted between July and August 2024, involving interviews with pharmacists from various Norwegian pharmacies. Transcripts were analysed to identify categories and themes. Ten pharmacists participated, and the data were structured into 19 categories grouped into six themes: (i) the concept and implementation of home pharmaceutical services, (ii) benefits, (iii) challenges, (iv) impact on daily practice and training needs, (v) evaluation and teamwork, and (vi) patient outcomes and the use of digital tools. Findings indicate that home-based pharmaceutical services could improve healthcare quality in Norway, but their implementation involves challenges such as resource limitations and training needs. Recommendations include developing targeted strategies and support mechanisms to overcome these barriers, in order to ensure optimal benefits while maintaining high standards in pharmaceutical home care services.